Occupational Health and Safety Analysis Using HIRA and AS/NZS 4360:2004 Standard at XYZ Shipyard - Mohammad Danil Arifin; Fanny Octaviani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
A shipyard is defined as a place where ships are repaired and built. Where, various risks from the work process i.e., ship repair, hull cleaning, hull coating, etc., exist. Therefore, it is necessary to carry out risk analysis in the work process at XYZ Shipyard. This study uses a descriptive method with a qualitative approach through interviews and based on hazard identification and risk assessment (HIRA) using the AS/NZS 4360:2004 standard to calculate the risk value. Occupational health and safety assessments are carried out to evaluate risks that exist in the workplace intending to eliminate, reduce, and replace sources of risk with safer equipment or processes, or to reduce risks to the health and safety of workers. In this study, we are focused on the three working processes i.e., ship repairment process, hull cleaning, and coating. As a result, it can be concluded that all the risks which occurred in the work process at XYZ Shipyard i.e., ship repair, hull cleaning, and coating process were controlled.